Cognitive Behavioral Counseling Guide with Cognitive Restructuring Techniques to Reduce Social Anxiety in Students Victims of Bullying - Ni Putu Harisila Mutari; Kadek Suranata; Putu Ari Dharmayanti; Ni Ketut Suarni; Nyoman Dantes (Department of Guidance and Counseling, FIP, Undiksha, 2023)
The problem of social anxiety experienced by students who are victims of bullying has become a major concern, given its negative impact on students' mental health and academic success. This study aims to develop the cognitive behavioral counseling Handbook with Cognitive Restructuring Techniques to Reduce Social Anxiety in Students Victims of Bullying. This research method uses research and development (R&D) with a 4D (Four D) model developed by Thiagarajan, using a questionnaire instrument. Expert testers on the guidance product involve 3 Guidance and Counselling experts. The results of this study show that (1) produce a cognitive behavioral counseling guidebook, (2) test the validity with the Lawshe formula for the content of the guidebook. The results of the content validity analysis obtained the result of CVR of each item more than 0 (CVR>0) and no items of smaller value were found; from 0 (CVR<0). The CVI score was obtained with a value of 1, then it can be interpreted that the feasibility of this guidebook is high to be developed, (3) the practicality test of the guidebook on the assessment of 4 counseling guidance practitioners was declared practical (88%), (4) the effectiveness of the guidebook obtained a sig value (2-tailed) of 0.000 < 0.05 or below 0.05 then a size effectiveness test was carried out to obtain a value of 5.183 This means that the implementation of cognitive behavioral counseling with cognitive restructuring techniques is effective for reducing social anxiety in students victims of bullying.